2020
DOI: 10.1371/journal.pone.0230134
|View full text |Cite
|
Sign up to set email alerts
|

Influence of observer-dependency on left ventricular hypertrabeculation mass measurement and its relationship with left ventricular volume and ejection fraction –  comparison between manual and semiautomatic CMR image analysis methods

Abstract: Background Recent studies concerning left ventricular noncompaction (LVNC) suggest that the extent of left ventricular (LV) hypertrabeculation has no impact on prognosis. The variety of methods of LV noncompacted myocardial mass (NCM) assessment may influence the results. Hence, we compared two methods of NCM estimation: largely observer-independent Hautvast's (H) computed algorithm-based approach and commonly used Jacquier's (J) method, and their associations with LV end-diastolic volume (EDV) and ejection fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 24 publications
0
1
0
Order By: Relevance
“…As reflected by the authors, Haut-vast´s algorithm has shown excellent reproducibility, given its semi-automatic and might be a solution to increase reproducibility and repeatability. The manuscript opens the debate about the correct quantification of the trabeculated mass and the diagnosis of LVNC [32,36,37].…”
Section: Cardiac Mri: Quantification Of the Mass And Late Gadolinium ...mentioning
confidence: 99%
“…As reflected by the authors, Haut-vast´s algorithm has shown excellent reproducibility, given its semi-automatic and might be a solution to increase reproducibility and repeatability. The manuscript opens the debate about the correct quantification of the trabeculated mass and the diagnosis of LVNC [32,36,37].…”
Section: Cardiac Mri: Quantification Of the Mass And Late Gadolinium ...mentioning
confidence: 99%